ANALISIS PEMAHAMAN GURU TERHADAP GAYA BELAJAR SISWA DI SDN 020 RIDAN PERMAI - Dina Hafizha; Rizki Ananda; Iis Aprinawati (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
This research was motivated by the importance of teacher's role in understanding students’ characteristics such as learning styles. This research was aimed to describe the teachers' understanding on students’ learning styles, learning profiles, services provided by teachers, problems faced by teachers, and teachers' efforts in solving difficulties of providing services on students’ learning styles at SDN 020 Ridan Permai. This research used a qualitative approach specifically descriptive design. The research finding showed the teachers of 2nd, 3rd. 4th, and 5th grade at SDN 020 Ridan Permai already understood the students' learning styles theoretically. The teacher's learning profile to facilitate students’ learning styles was quite good, but it still needs to be improved by using more varied learning methods, as well as providing relevant learning media. Based on the 15 aspects observed, teachers of 2nd and 3rd grade have implemented 13 aspects, 4th grade teacher have implemented all aspects, and 5th grade teacher have implemented 12 aspects.  In addition, the teacher’s difficulties were rarely to use proyektor in the learning process, adversity in facilitating students’ learning of auditory styles, adversity in managing time, and students might not understand the subject matter fully. The efforts’ made by teachers in solving the obstacles faced in providing services to student learning styles include being disciplined on time, learning from previous experiences and keeping up with the times, increasing insight of students’ learning style differences, bounding collaboration among teachers, students and parents and add further information which was relevant.